Novel Drug Targets for Ischemic Stroke Identified Through Mendelian Randomization Analysis of the Blood Proteome. Issue 10 (3rd September 2019) - Chong, Michael; Sjaarda, Jennifer; Pigeyre, Marie; Mohammadi-Shemirani, Pedrum; Lali, Ricky; Shoamanesh, Ashkan; Gerstein, Hertzel Chaim; Paré, Guillaume
Abstract : Background: Novel, effective, and safe drugs are warranted for treatment of ischemic stroke. Circulating protein biomarkers with causal genetic evidence represent promising drug targets, but no systematic screen of the proteome has been performed. Methods: First, using Mendelian randomization (MR) analyses, we assessed 653 circulating proteins as possible causal mediators for 3 different subtypes of ischemic stroke: large artery atherosclerosis, cardioembolic stroke, and small artery occlusion. Second, we used MR to assess whether identified biomarkers also affect risk for intracranial bleeding, specifically intracerebral and subarachnoid hemorrhages. Third, we expanded this analysis to 679 diseases to test a broad spectrum of side effects associated with hypothetical therapeutic agents for ischemic stroke that target the identified biomarkers. For all MR analyses, summary-level data from genome-wide association studies (GWAS) were used to ascertain genetic effects on circulating biomarker levels versus disease risk. Biomarker effects were derived by meta-analysis of 5 GWAS (N⩽20 509). Disease effects were derived from large GWAS analyses, including MEGASTROKE (N⩽322 150) and UK Biobank (N⩽408 961) studies. Results: Several biomarkers emerged as causal mediators for ischemic stroke. Causal mediators for cardioembolic stroke included histo-blood group ABO system transferase, coagulation factor XI, scavenger receptor class A5 (SCARA5), and tumor necrosis factor–like weak inducer of apoptosis (TNFSF12). Causal mediators for large artery atherosclerosis included ABO, cluster of differentiation 40, apolipoprotein(a), and matrix metalloproteinase-12. SCARA5 (odds ratio [OR]=0.78; 95% CI, 0.70–0.88; P =1.46×10 −5 ) and TNFSF12 (OR=0.86; 95% CI, 0.81–0.91; P =7.69×10 −7 ) represent novel protective mediators of cardioembolic stroke. TNFSF12 also increased the risk of subarachnoid (OR=1.53; 95% CI, 1.31–1.78; P =3.32×10 −8 ) and intracerebral (OR=1.34; 95% CI, 1.14–1.58; P =4.05×10 −4 ) hemorrhages, whereas SCARA5 decreased the risk of subarachnoid hemorrhage (OR=0.61; 95% CI, 0.47–0.81; P =5.20×10 −4 ). Multiple side effects beyond stroke were identified for 6 of 7 biomarkers, most (75%) of which were beneficial. No adverse side effects were found for coagulation factor XI, apolipoprotein(a), and SCARA5. Conclusions: Through a systematic MR screen of the circulating proteome, causal roles for 5 established and 2 novel biomarkers for ischemic stroke were identified. Side-effect profiles were characterized to help inform drug target prioritization. In particular, SCARA5 represents a promising target for treatment of cardioembolic stroke, with no predicted adverse side effects. Abstract : Supplemental Digital Content is available in the text.